Reproduction and embryogenesis of the mandi‐amarelo catfish, Pimelodus maculatus (Pisces, Pimelodidae), in captivity. (21st May 2012) - Arantes, F. P.; Borçato, F. L.; Sato, Y.; Rizzo, E.; Bazzoli, N.
Summary To study reproduction and embryogenesis, Pimelodus maculatus specimens were kept in captivity and captured bimonthly during 1 year. Gonads samples (211 specimens) were collected and submitted to routine histological techniques. Pimelodus maculatus prepared to reproduce when water temperature was high, and even reached advanced maturation but did not spawn in captivity. Spent fish gonads were not documented, and atretic follicles were frequent (60%) in late maturation females. When then submitted to hypophysation, 70% of the females responded positively to hormonal treatment. Oocyte extrusion occurred 8 h after a second hormonal injection at 26°C. The fertilisation rate was 65.1 ± 9.2% at 24°C. Recently spawned oocytes of P. maculatus were spherical, non‐adhesive, yellow in colour, with an average diameter of 1113.92 ± 37.02 μm and covered by a thick gelatinous layer. Blastopore closure occurred 7 h and 30 min after fertilisation. Embryonic development was completed within 18 h after fertilisation. The results of this work provide important knowledge for the handling and cultivation of not only P. maculatus, but other species of potential value for fish culture.